Harmony of Tradition and Modernity: The Acculturation of Kejawen Culture in Malang City from the Perspective of Urban Society. - Tasya Arifah Rahmadita; Sarmini (Universitas Telkom, 2026)
This study aims to analyze the process of acculturation between Kejawen culture and modernity within the urban society of Malang City. Amid the currents of globalization and urbanization, Kejawen traditions face the challenge of maintaining their existence without losing their core values. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observations, and document studies involving community leaders, youth, and cultural practitioners. The findings reveal that acculturation occurs harmoniously through symbolic transformation, revitalization of cultural practices, and the utilization of digital media. Kejawen culture continues to thrive by adapting to the modern context while preserving its spiritual meaning and embedded local wisdom. This study emphasizes the importance of community-based preservation strategies and the integration of local cultural values into multicultural education as efforts to streng then cultural identityamid societal changes.